Corporate Social Performance: Past and Present Areas of Commitment - Holmes, Sandra L. (Academy of Management Journal, 1977)
An investigation of the social activities of 192 Fortune corporations reveals pronounced patterns of involvement across industry classifications and provides evidence of increasing ?specialization? of corporate social interests. Such specialization is at least partially explained by management's desires to utilize the industry's special skills in social as well as economic activities.